下肢康复机器人联合头针治疗对老年缺血性卒中患者步行效率和协调功能影响调查 The Effects of Lower Limb Rehabilitation Robot Combined with Scalp Acupuncture on the Walking Efficiency and Coordination Function in Elderly Patients with Ischemic Stroke - 张梦若1，徐守臣2，隋翠翠1，李玉奎1，王雪莉1 (ZHANG Mengruo1, XU Shouchen2, SUI Cuicui1, LI Yukui1, WANG Xueli1 ) (Zhongguo cuzhong zazhi, 2024)
目的 分析下肢康复机器人联合头针治疗对老年缺血性卒中患者步行效率和协调功能的影响。